Paternal obesity negatively affects male fertility and assisted reproduction outcomes: a systematic review and meta-analysis. Issue 5 (November 2015) - Campbell, Jared M.; Lane, Michelle; Owens, Julie A.; Bakos, Hassan W.
Abstract: This systematic review investigated the effect of paternal obesity on reproductive potential. Databases searched were Pubmed, Ovid, Web of Science, Scopus, Cinahl and Embase. Papers were critically appraised by two reviewers, and data were extracted using a standardized tool. Outcomes were: likelihood of infertility, embryo development, clinical pregnancy, live birth, pregnancy viability, infant development, sperm; concentration, morphology, motility, volume, DNA fragmentation, chromatin condensation, mitochondrial membrane potential (MMP), and seminal plasma factors. Thirty papers were included, with a total participant number of 115, 158. Obese men were more likely to experience infertility (OR = 1.66, 95% CI 1.53–1.79), their rate of live birth per cycle of assisted reproduction technology (ART) was reduced (OR = 0.65, 95% CI 0.44–0.97) and they had a 10% absolute risk increase of pregnancy non-viability. Additionally, obese men had an increased percentage of sperm with low MMP, DNA fragmentation, and abnormal morphology. Clinically significant differences were not found for conventional semen parameters. From these findings it can be concluded that male obesity is associated with reduced reproductive potential. Furthermore, it may be informative to incorporate DNA fragmentation analysis and MMP assessment into semen testing, especially for obese men whose results suggest they should have normal fertility.